Causality between Frequency of Visit with Tourists Satisfaction: a Multi-group Analysis - Kencana, Eka N.; Darmayanti, Trisna (Udayana Journal of Social Sciences and Humanities, 2017)
This work is aimed to study the causal relationship between frequencies of visit to Bali with tourists’ satisfaction regarding the quality of destination. An instrument with five Likert-scale options was designed to measure visitors’ perception. The respondents in this study are 150 tourists who visited Kuta and Nusa Dua areas in September— October 2016, two famous tourist destinations in Bali; consists of 75 foreign and domestic tourists, respectively. The respondents were asked for their satisfaction and quality of destination had been visited. By applying structural equation modeling with multi-group analysis (MGA-SEM), the result shows the quality of destination significantly affects their satisfaction. In addition, satisfaction level for repeater guests is smaller compared to tourists’ who visited the destination for the first time.